Study on Oviposition and Hatching Period in Rhipicephalus (Boophilus) Microplus (Acari: Ixodidae) under Laboratory Conditions - Singh, Ritika; Bagherwal, RK; Jayraw, AK; Chaudhary, Nidhi S; Akil, MD (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
Ticks are highly specialized distributed worldwide obligate hematophagous ectoparasites of mammals, birds, and reptiles.